1999
DOI: 10.1017/s0958067099018953
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Effect on the Rates of Isometric Force Development and Relaxation in the Fresh and Fatigued Human Adductor Pollicis Muscle

Abstract: summaryThe purpose of the present study was to investigate the effect of temperature on the rates of isometric force development and relaxation in electrically activated fresh and fatigued human adductor pollicis muscle. Following immersion of the lower arm for 20 min in water baths of four different temperatures, muscle temperatures were approximately 37, 31, 25 and 22°C. Maximal isometric force was reduced by 16·8 ± 1·5% at 22°C. The stimulation frequency-force and -rate of force development relationships we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
103
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(117 citation statements)
references
References 17 publications
9
103
0
3
Order By: Relevance
“…In laboratory tasks, however, these phases may be separated by asking the subjects to perform accurate alternating phases of force increase and decrease that require agonist muscle contraction and relaxation respectively. A few studies explored the control of accurate muscle relaxation tasks at various rates (Häkkinen & Komi, 1986; Ruiter, Jones, Sargeant, & Haan, 1999; Schieppati & Crenna, 1984; Shim, Olafsdottir, Zatsiorsky, & Latash, 2005b). In the study by Shim and colleagues, accuracy of performance during accurate ramp-like force decrease was worse than during force increase for slow tasks and better than during force increase with very short ramp times.…”
Section: Discussionmentioning
confidence: 99%
“…In laboratory tasks, however, these phases may be separated by asking the subjects to perform accurate alternating phases of force increase and decrease that require agonist muscle contraction and relaxation respectively. A few studies explored the control of accurate muscle relaxation tasks at various rates (Häkkinen & Komi, 1986; Ruiter, Jones, Sargeant, & Haan, 1999; Schieppati & Crenna, 1984; Shim, Olafsdottir, Zatsiorsky, & Latash, 2005b). In the study by Shim and colleagues, accuracy of performance during accurate ramp-like force decrease was worse than during force increase for slow tasks and better than during force increase with very short ramp times.…”
Section: Discussionmentioning
confidence: 99%
“…The onset of torque development was defined as the point at which torque exceeded 2% of peak torque for a given contraction. Peak RTD was also normalized relative to peak torque of that contraction (RTD rel ) to control for variation between subjects in muscle size and strength (21, 36, 49), as we observed that peak RTD was related to overall peak torque and muscle size (see Results, 3.2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Of the many forms of cryotherapy used to this end, CWI is the most popular in the literature and in practice [2]. Several studies have investigated [5-11] and reviewed [2,3,12-14] the effects of CWI for reducing soreness and speeding the recovery of force-generating capacity by skeletal muscles following stressful bouts of exercise. However, evidence regarding the efficacy of CWI, and cryotherapy in general, to speed recovery remains equivocal.…”
Section: Reviewmentioning
confidence: 99%
“…CWI may restore vagal tone and normalize parasympathetic modulation of heart rate following intense exercise [11,72-74]. Heart rate recovery and heart rate variability indices seem to be improved by immersion of subjects in thermoneutral (34°C) or CWI (15°C) temperatures compared to no immersion [73].…”
Section: Reviewmentioning
confidence: 99%